Complementary religious and spiritual interventions in physical health and quality of life: A systematic review of randomized controlled clinical trials. - Juliane Piasseschi de Bernardin Gonçalves; Giancarlo Lucchetti; Paulo Rossi Menezes; Homero Vallada (PLoS ONE)
Objective To examine whether religious and spiritual interventions (RSIs) can promote physical health and quality of life in individuals. Methods The following databases were used to conduct a systematic review: PubMed, Scopus, Web of Science, EMBASE, PsycINFO, Cochrane, and Scielo. Randomized controlled trials that evaluated RSIs regarding physical health outcomes and/or quality of life in English, Spanish or Portuguese were included. RSI protocols performed at a distance (i.e. intercessory prayer) or for psychiatric disorders were excluded. This study consisted of two phases: (a) reading titles and abstracts, and (b) assessing the full articles and their methodological quality using the Cochrane Back Review Group scale. Results In total, 7,070 articles were identified in the search, but 6884 were excluded in phase 1 because they were off topic or repeated in databases. Among the 186 articles included in phase 2, 140 were excluded because they did not fit the inclusion criteria and 16 did not have adequate randomization process. Thus, a final selection of 30 articles remained. The participants of the selected studies were classified in three groups: chronic patients (e.g., cancer, obesity, pain), healthy individuals and healthcare professionals. The outcomes assessed included quality of life, physical activity, pain, cardiac outcomes, promotion of health behaviors, clinical practice of healthcare professionals and satisfaction with protocols. The divergence concerning scales and protocols proposed did not allow a meta-analysis. RSIs as a psychotherapy approach were performed in 40% of the studies, and the control group was more likely to use an educational intervention (56.7%). The results revealed small effect sizes favoring RSIs in quality of life and pain outcomes and very small effects sizes in physical activity, promotion of health behaviors and clinical practice of health professionals compared with other complementary strategies. Other outcomes, such as cardiac measures and satisfaction with the protocols, revealed no evidence for RSIs. Regarding the quality of the selected articles according to the Cochrane Back Review Group Scale, the average score was 6.83 (SD = 9.08) on a scale of 11, demonstrating robustness in the studies. Conclusion Clinical trials on RSIs demonstrated that they had small benefits compared with other complementary health therapies by reducing pain and weight, improving quality of life and promoting health behaviors. The lack of clinical trials that included biological outcomes and the diversity of approaches indicate a need for more studies to understand the possible mechanisms of action of RSIs and their roles in health care.